PENGELOLAAN.ANGGARAN PENDAPATAN,DAN BELANJA DESA (APB DESA))TAHUN ANGGARAN 2018 DAN.2019 DALAM PEMBERDAYAAN PROGRAM TERNAK BABI TERINTEGRASI (TERBIT) DI.DESA CAU. BELAYU.KECAMATAN MARGA.KABUPATEN .TABANAN BALI - Suarningsih, Ni Luh Gede; Supriliyani, Ni Wayan; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2021)
The management of the village income and expenditureEbudget (APB Desa) for the 2018 and 2019 fiscal years in Cau Belayu Village finances.one of the village expenditures in the field of community empowerment, namely the Ternak Babi Terintegrasi program (TERBIT). Budget management that has been carriedsout for 2 fiscal yearstin the realization of the TERBIT program has resulted in a surplus of considerable value. The-research method used in this research is the descriptive qualitative method. The analysis used is the management indicator according to Adisasmita, namely planning, implementation, and supervision. The results.of this study indicate that budget managementsin the funding of the TERBIT program is quite appropriate in accommodating community empowerment. Budget management is expected to absorb the entire budgeted funds, however inadequate planning and a much smaller realization value cause a fairly large surplus in the 2 years of budget realization. Keywords: Management, Budget, Realization, Ternak Babi Terintegrasi (TERBIT)